Students' and teachers' perception on the learning of Qin and Jiangnan school erhu performance styles - Loo, Fung Ying; Loo, Fung Chiat; Xi, Chen (2016)
The Qin and Jiangnan Pai schools of erhu playing reveal two different performing styles, each with its own unique skills and requirements. In past literature, some scholars looked into each school of erhu playing. However, there is a lack of research on the teaching the Qin and Jiangnan Pai schools of erhu playing especially in terms of how much the students are able to manage the various musical parameter. This research examined the perception of both students and teachers in the learning of Qin and Jiangnan Pai schools of erhu. How students perceived the various musical elements necessary in executing both styles of erhu playing was investigated. Teachers’ perception on teaching both erhu styles of playing was also investigated. The outcome of this research shows the level of understanding among students in terms of the various musical parameters discussed, and a comparison to teachers’ feedback.